PET FASHION SEBAGAI GAYA HIDUP - Ulfa Septiana (Fesyen Perspektif, 2017)
The existence of various competitions such as the pet show, fancy cat, dog fancy, dog shows in Indonesia has developed a pet shop industry which was originally only sold for animal nutrition purposes, now also provides clothing and accessories for pets. The phenomenon is interesting to study to get an overview of the development of pet fashion both in Indonesia and in the world. Pet fashion industry is currently booming due to get a lot of consumers who want to express themselves through their favorite animal, so that it becomes a lifestyle. Pet fashion is a lifestyle property of humans because animals can not choose the style and taste for fashion to be expressed. Pet fashion developments accompanied with pro and contradiction, but still flowing in line with the development of modern lifestyles that increasingly individualized society.